Study on spatial and temporal mobility pattern of urban taxi services - Genlang Chen; Xiaogang Jin; Jiangang Yang (2010 IEEE International Conference on Intelligent Systems and Knowledge Engineering, 2010)
The analysis of human behavior is the basis of understanding many social phenomena. Based on a large database of taxi billing system, this paper provides an analysis of human mobility data in an urban area of using taxi services in Shanghai. By studying the spatial temporal data of taxi services, it shows that the distribution of running time interval is approximated by Power-law distribution. And it also reflects that the taxi services may have the short-time and small-scaled characteristics, which seems to be consistent with human travel patterns.